Evaluation of Laboratory Activities and Students’ Self-Regulated Learning Using an Inquiry-Based Approach - Yunita Arian Sani Anwar; Agus Abhi Purwoko; Muti'ah Muti'ah; Eka Junaidi; Lalu Rudyat Telly Savalas; Nadia Rizki Hutami (Jurnal Pendidikan MIPA, 2026)
This study aims to examine the effects of guided inquiry and open inquiry approaches on students’ laboratory activity scores and self-regulated learning in chemistry instruction. A quasi-experimental research design was employed, involving two groups: a guided inquiry group consisting of 25 students and an open inquiry group consisting of 23 students. Laboratory activity was assessed using a rubric covering pre-lab, lab work, and post-lab activities. A questionnaire was used to measure students’ SRL across five dimensions: metacognitive skills, time management, environmental structuring, persistence, and help-seeking. The results showed that the guided inquiry group achieved the highest laboratory activity and SRL scores. The pre-lab, lab-work, and post-lab scores were consistent with the group’s overall laboratory activity score. Among SRL dimensions, the highest scores in the guided inquiry group were observed for metacognitive skills and environmental structuring. In contrast, the open inquiry group showed the highest SRL score in the help-seeking dimension. ANCOVA analysis revealed a significant relationship between the inquiry approach and both laboratory activity scores and students’ SRL. Students' tendency to experience difficulty initiating the investigative stages contributed to the lower effectiveness of open inquiry. These findings indicate that the effectiveness of guided inquiry is attributed to its structured support, which facilitates students in initiating the investigative phase. In contrast, although open inquiry provides greater opportunities for exploration, its limited implementation in instructional practice may impede students’ ability to effectively initiate the investigative process. Keywords: inquiry approach, chemistry instruction, metacognition, motivation, pre-laboratory.